algebra

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x

could some one check this for me please

asked by Ashley
  1. You can check yourself by multiplying -6x^2(2x^4+24x^3-3x)

    posted by Anonymous
  2. -12x^6+24x^5-18x^2=2x^4+4x^3+3x
    could some one tell me if the answer is right. Please help I am not good with sign confused.

    posted by Ashley

Respond to this Question

First Name

Your Response

Similar Questions

  1. alg2 check?

    solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem? I said the 46 going to 48 and subtracting the 6 from 48?
  2. algebra

    Did I do this problem the correct way if so is there a shorter way to explain this? x(x + 6)(x + -4) = 24x x(6 + x)(x + -4) = 24x x(6 + x)(-4 + x) = 24x (6 + x) * (-4 + x x(6(-4 + x) + x(-4 + x)) = 24x x((-4 * 6 + x * 6) + x(-4 +
  3. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  4. Algebra (Re.: Reiny)

    The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 +
  5. Math

    (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me? thank you!
  6. Algebra

    checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
  7. algebra

    -12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.
  8. Algebra 1

    Rewrite the polynomial in descending order in its simplest form. here is #1 12x^2 y^2 z^3+2+24x^2 I think it should be writen 12x^2y^2Z^3+24x^2+2 then there is also question #6 I need help with is it x+y+xy+3x+4x^2 I think it
  9. math

    -12x^6+24x^5-18x^2/-6x^2= -4x^8+4x^7-3x tell me if this right
  10. Math

    Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2

More Similar Questions